Engaging Seniors with Dementia through Music and Movement - Poon Chiew Hwa; Cheong Ku Wing (Wacana Seni Journal of Arts Discourse, 2024)
Music and movement activities are widely recognised for enhancing the well-being of patients with dementia, yet specifics regarding session content are often lacking in discussions. This paper investigates the effectiveness and suitability of content within music and movement sessions through action research employing two cycles of planning, acting, developing, and reflecting. Session content includes planning, strategies, physical movements, and music selections. A series of eight 45-minute sessions were conducted for a group of 10 to 15 dementia patients at the Alzheimer’s Disease Foundation Malaysia in Petaling Jaya. This action research gathered qualitative data through participatory observations, reflective diaries, and video recordings. Findings indicate that patient engagement levels varied based on familiarity with music selections; many patients embraced children’s songs regardless of age and learned new compositions. Movement options were constrained to sitting due to the patient physical condition. Lesson plan outlines evolved over sessions, offering insights and recommendations for future music and movement practitioners.